PENGARUH KOMPETENSI DAN PENGALAMAN KERJA DI KPP PRATAMA JAKARTA PANCORAN - Muhammad Rifqi Fahreza (2021)
This study is a quantitative study that aims to determine the effect of competence and work experience on employee performance at KPP Pratama Jakarta Pancoran. The population in this study were all employees of KPP Pratama Jakarta Pancoran totaling 113 employees. The number of samples used in this study was 88 employees using the slovin formula. The data used in this study is primary data, namely by distributing questionnaires. The data analysis technique used in this research is the quantitative data analysis technique using statistical methods. The statistical method used is Partial Least Square (PLS). The test results obtained (1) competence has a positive and significant effect on the performance of KPP Pratama Jakarta Pancoran employees, (2) work experience has a positive and significant effect on the performance of KPP Pratama Jakarta Pancoran employees.